How we developed a comprehensive resuscitation-based simulation curriculum in emergency medicine. (2nd January 2016) - Dagnone, Jeffrey Damon; McGraw, Robert; Howes, Daniel; Messenger, David; Bruder, Eric; Hall, Andrew; Chaplin, Timothy; Szulewski, Adam; Kaul, Tom; O'Brien, Terrence
Abstract: Over the past decade, simulation-based education has emerged as a new and exciting adjunct to traditional bedside teaching and learning. Simulation-based education seems particularly relevant to emergency medicine training where residents have to master a very broad skill set, and may not have sufficient real clinical opportunities to achieve competence in each and every skill. In 2006, the Emergency Medicine program at Queen's University set out to enhance our core curriculum by developing and implementing a series of simulation-based teaching sessions with a focus on resuscitative care. The sessions were developed in such as way as to satisfy the four conditions associated with optimum learning and improvement of performance; appropriate difficulty of skill, repetitive practice, motivation, and immediate feedback. The content of the sessions was determined with consideration of the national training requirements set out by the Royal College of Physicians & Surgeons of Canada. Sessions were introduced in a stepwise fashion, starting with a cardiac resuscitation series based on the AHA ACLS guidelines, and leading up to a more advanced resuscitation series as staff became more adept at teaching with simulation, and as residents became more comfortable with this style of learning. The result is a longitudinal resuscitation curriculum that begins with fundamental skills of resuscitation and crisis resource management (CRM) in the first 2 years of residency and progresses through increasingly complex resuscitation cases where senior residents are expected to play a leadership role. This paper documents how we developed, implemented, and evaluated this resuscitation-based simulation curriculum for Emergency Medicine postgraduate trainees, with discussion of some of the challenges encountered.